The Effect of Work-Life Balance and Spiritual Intelligence on Organizational Citizenship Behavior Mediated by Organizational Commitment - Janartika Murwaningsih; Lie Liana (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates the influence of work-life balance (WLB) and spiritual intelligence on organizational citizenship behavior (OCB), with organizational commitment as a mediating factor, in the context of Islamic banking. The competitive nature of the banking industry, particularly for Islamic banks, requires effective human resource management to enhance organizational performance and employee contributions beyond formal roles. Employees' ability to balance professional and personal lives and their spiritual intelligence are critical factors in fostering positive organizational behaviors. Using a purposive sampling technique, 139 married employees with more than one year of service. This criterion was chosen to ensure the respondents had sufficient experience and personal stability to reflect the dynamics of WLB and organizational commitment. The results reveal significant positive relationships between WLB, spiritual intelligence, and OCB, both directly and mediated by organizational commitment. These findings offer valuable insights for human resource management in Islamic banking to strengthen employee engagement and organizational effectiveness.